2020
DOI: 10.26911/thejhpb.2020.05.01.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effectivity of Peer Education Module on Knowledge, Attitude, and Fast Food Consumption in Adolescents

Abstract: Background: Increasing obesity sufferers every year, in a few decades becomes an important problem. Increased obesity can lead to an increased risk of degenerative diseases which can cause death. Several attempts have been made to prevent and treat obesity. The purpose of this study is to determine the effectiveness of peer education on knowledge, attitudes, and consumption of fast food in adolescents. Subjects and Method: This study is a randomized controlled trial conducted at a Junior High School (SMP Neger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Additionally, the outcomes of this study have demonstrated that the intervention program significantly elevated awareness regarding the detrimental effects of fast-food consumption. Pertinent to this study, Manggabarani et al [ 32 ] conducted research focusing on the impact of peer-based education on knowledge, attitude, and consumption of fast food among teenagers. The educational intervention had a marked effect on augmenting both attitude and knowledge levels pertaining to nutrition post-training.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the outcomes of this study have demonstrated that the intervention program significantly elevated awareness regarding the detrimental effects of fast-food consumption. Pertinent to this study, Manggabarani et al [ 32 ] conducted research focusing on the impact of peer-based education on knowledge, attitude, and consumption of fast food among teenagers. The educational intervention had a marked effect on augmenting both attitude and knowledge levels pertaining to nutrition post-training.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by (Lee et al, 2022) indicated that students, especially those living away from their families, rely on fast food as a primary food source. (Manggabarani et al, 2020) suggests that Malaysian fast-food consumers have become more focused on factors like product cleanliness, taste, ambiance, and freshness before making a purchase decision. These considerations significantly shape their attitudes as fast-food consumers.…”
Section: Literature Review University Students' Attitudes On Fast Foo...mentioning
confidence: 99%
“…Aktifitas fisik remaja di Kelurahan Bunut Barat yang rendah menayebabkan energy yang dikeluarkan jauh lebih rendah dari asupan energy dan kalori yang masuk kedalam tubuh remaja. Kurangnya aktifitas fisik dan kelebihan asupan energy dan lemak berpengaruh terhadap kejadian obesitas [15]. Aktifitas fisik yang kurang aktif dengan asupan energi yang tinggi dapat menyebabkan resiko obesitas 4 kali lebih tinggi dibandingkan aktifitas fisik yang sangat aktif dengan asupan energi yang tinggi.…”
Section: Faktor Yang Berhubungan Dengan Obesitas Remaja…( Leli Sopiah...unclassified